2008
DOI: 10.1182/asheducation-2008.1.427
|View full text |Cite
|
Sign up to set email alerts
|

Novel Agents in CML Therapy: Tyrosine Kinase Inhibitors and Beyond

Abstract: The emergence of resistance to imatinib has become a significant problem despite the remarkable clinical results achieved with this tyrosine kinase inhibitor in the treatment of chronic myeloid leukaemia. The most common cause of imatinib resistance is the selection of leukemic clones with point mutations in the Abl kinase domain. These mutations lead to amino acid substitutions and prevent the appropriate binding of imatinib. Genomic amplification of BCR-ABL, modulation of drug efflux or influx transporters, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 73 publications
0
33
0
3
Order By: Relevance
“…2,3 However, molecular studies of imatinib-treated patients in remission demonstrated that Bcr-Abl expression is still detectable in most cases, and discontinuation of imatinib therapy often results in disease relapse. 4,5 Limited duration of imatinib response is also common in advanced CML patients, and imatinib resistance can occur at any stage of the disease. 5,6 Acquired imatinib resistance and disease progression are frequently characterized by Bcr-Abl mutations and posttranslational modifications that affect imatinib binding and kinase inhibition.…”
mentioning
confidence: 99%
“…2,3 However, molecular studies of imatinib-treated patients in remission demonstrated that Bcr-Abl expression is still detectable in most cases, and discontinuation of imatinib therapy often results in disease relapse. 4,5 Limited duration of imatinib response is also common in advanced CML patients, and imatinib resistance can occur at any stage of the disease. 5,6 Acquired imatinib resistance and disease progression are frequently characterized by Bcr-Abl mutations and posttranslational modifications that affect imatinib binding and kinase inhibition.…”
mentioning
confidence: 99%
“…While the introduction of the Bcr-Abl kinase inhibitor, imatinib, into the clinical armamentarium, represents an important advance in the treatment of CML, the development of drug resistance constitutes a significant barrier to curing this disease (2,17). The present study demonstrated that treatment with the HDACi, SAHA (0.5-8 µM), induced cell death in imatinib-sensitive K562 cells, as well as imatinib-resistant K562G cells, in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 59%
“…The current recommended first line therapy for patients with newly diagnosed CML, is imatinib. However, resistance to imatinib is a significant problem, despite the good clinical results achieved with this tyrosine kinase inhibitor in the treatment of CML (2). Therefore, the identification of novel therapeutic agents, in addition to an understanding of their underlying mechanisms, is necessary in order to improve the outcome in patients with CML.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its therapeutic efficacy, the development of imatinib-resistance and intolerance is still a challenging problem for most patients (7). Many novel compounds and therapeutic approaches are currently being investigated preclinically and clinically to overcome imatinib resistance (8). Dasatinib and nilotinib are the second generation TKIs that are more effective and safer in patients with imatinib-resistance and intolerance (8).…”
Section: Introductionmentioning
confidence: 99%
“…Many novel compounds and therapeutic approaches are currently being investigated preclinically and clinically to overcome imatinib resistance (8). Dasatinib and nilotinib are the second generation TKIs that are more effective and safer in patients with imatinib-resistance and intolerance (8). However, the development of novel Bcr-Abl mutants resistant to these new small-molecule inhibitors and adverse effects of these agents are still significant problems (9).Therefore, alternative therapeutic approaches are required and natural products have been investigated because of their potential in cancer prevention and treatment.…”
Section: Introductionmentioning
confidence: 99%